DEFORESTATION, DEGRADATION, AND FOREST REGROWTH IN INDONESIAÃ¢â¬â¢S PROTECTED AREAS FROM 2000-2010 - Erik Meijaard, Douglas Fuller J. Miettinen (Indonesian Journal of Conservation, 2013)
This research used two new land cover maps from 2000 and 2010 to examine recent changes in forest cover in IndonesiaÃ¢â¬â¢s protected areas (PAs). Our analysis included national parks (NPs), and nature and wildlife reserves (NRs/WSs) where deforestation was detected from 2000-2010. IndonesiaÃ¢â¬â¢s terrestrial PAs lost approximately 0.37 million hectares (Mha), or 2.6% of their 2000 forest cover by 2010; with an additional 0.71 Mha transition from forest to the plantation/regrowth class. Although the forest regrowth of 0.57 Mha recorded during the same time frame suggests wide spread recovery of areas degraded prior to 2000, the high levels of transition from forest to plantation/regrowth class indicate that forest degradation within the protected areas is still a significant problem. Despite some improvement relative to the 1990s, we conclude that much improved management is required to address continued deforestation and degradation in IndonesiaÃ¢â¬â¢s PAs. Keywords: Conservation Policy, Deforestation, Indonesia, Illegal Logging, Land Cover Change, MODIS Satellite Imagery ÃÂ  Penelitian ini menggunakan dua peta tutupan lahan baru dari tahun 2000 dan 2010 untuk memeriksa perubahan terbaru dalam tutupan hutan di kawasan lindung di Indonesia (KL). Unit analisis meliputi taman nasional (TN), serta cagar alam dan suaka margasatwa (CA / SM) di mana deforestasi terdeteksi 2000-2010. Di Indonesia terestrial KL kehilangan sekitar 0.370.000 hektar (Mha), atau 2,6% dari tutupan hutan tahun 2000 dibandingkan tahun 2010, dengan tambahan 0,71 juta ha transisi dari hutan ke kelas perkebunan / pertumbuhan kembali. Meskipun pertumbuhan kembali hutan 0,57 juta ha direkam selama waktu yang sama kajian menunjukkan pemulihan tersebar luas areal terdegradasi sebelum tahun 2000, tingginya tingkat transisi dari hutan ke kelas perkebunan / pertumbuhan kembali menunjukkan bahwa degradasi hutan di wilayah yang dilindungi masih merupakan masalah yang signifikan. Meskipun beberapa perbaikan secara relative melebihi era 1990-an, penelitian ini menyimpulkan bahwa manajemen ditingkatkan banyak yang dibutuhkan untuk mengatasi lanjutan deforestasi dan degradasi di lindung di Indonesia.Kata kunci: Kebijakan Konservasi, Deforestasi, Indonesia, Illegal Logging, Perubahan Tutupan Lahan, Citra Satelit MODIS ÃÂ